2007
DOI: 10.1196/annals.1384.002
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Targets in Saliva

Abstract: Saliva, the most accessible and noninvasive biofluid of our body, harbors a wide spectrum of biological analytes informative for clinical diagnostic applications. While proteomic constituents are a logical first choice as salivary diagnostic analytes, genomic targets have emerged as highly informative and discriminatory. This awareness, coupled with the ability to harness genomic information by high-throughput technology platforms such as genome-wide microarrays, ideally positions salivary genomic targets for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 25 publications
0
49
0
3
Order By: Relevance
“…This may be because the amount of total RNA is not abundantly present in sweat and semen samples or that the RNA extracted from saliva and vaginal ‰uid also contained RNA from oral and vaginal epithelium. Additionally, it was also reported that about 3000 diŠerent types of RNA exist in saliva 16) . Therefore, it is believed that large amounts of varying RNA types exist in saliva and vaginal ‰uid.…”
Section: Resultsmentioning
confidence: 99%
“…This may be because the amount of total RNA is not abundantly present in sweat and semen samples or that the RNA extracted from saliva and vaginal ‰uid also contained RNA from oral and vaginal epithelium. Additionally, it was also reported that about 3000 diŠerent types of RNA exist in saliva 16) . Therefore, it is believed that large amounts of varying RNA types exist in saliva and vaginal ‰uid.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-specific cell-free DNA has also been found in the circulation in many kinds of tumors. The presence of placental and tumor-specific cell-free RNA in plasma was also found (15).…”
Section: Extracellular Dna and Rnamentioning
confidence: 94%
“…In 2005, Juusola and Ballantyne demonstrated the distinction of stains originating from different body fluids such as blood, semen, saliva and vaginal secretions (59). But the main part of the RNA preserved in salivary stains is cellular (15).…”
Section: Extracellular Dna and Rnamentioning
confidence: 99%
See 2 more Smart Citations